Inovasi Web Microlearning untuk Menumbuhkan Jiwa Kewirausahaan Mahasiswa Vokasi Melalui Penerapan Pembelajaran Kooperatif Berbasis Proyek - Sahria, Yoga; Santosa, Budi; Muclas, Muclas; Kuat, Tri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Vocational education plays an important role in producing young generations who are ready to enter the workforce and become entrepreneurs. This study aims to develop microlearning web innovations to foster the entrepreneurial spirit of vocational students through the implementation of project-based cooperative learning. The research method used is a three-stage development, namely: (1) analysis of needs and design of microlearning web, (2) development of microlearning web, and (3) evaluation of microlearning web. This development process is carried out using the ADDIE Instructional Model. The results of the study indicate that the developed microlearning web is effective in fostering the entrepreneurial spirit of vocational students through the implementation of project-based cooperative learning. This is evidenced by the increase in questionnaire scores, observation results, and project products produced by students. This microlearning web can be an alternative innovative and interesting learning media for vocational students to improve their knowledge, Skills, and entrepreneurial Attitudes.